ANALISIS PENGOLAHAN LIMBAH CAIR RUMAH SAKIT DENGAN MENGGUNAKAN SISTEM BIOFILTER ANAEROB-AEROB SEBAGAI POTENSI RANCANGAN LEMBAR KERJA SISWA BIOLOGI SMK - Suwondo "; Wan Syafi'i; Rama Febriza Amethys (Biogenesis, 2017)
ABSTRACT This research to find out the quality of hospital wastewater treatment systems with anaerobic-aerobic biofilter for design student worksheet conducted in November 2015 to January 2016. This type of research is descriptive research with field survey methods. Many samples 2 samples with pick-up points at the inlet and outlet IPAL anaerobic-aerobic biofilter system at one hospital in Pekanbaru. The collection of data with a survey method, in which the waste water samples taken at the inlet and outlet IPAL anaerobic-aerobic biofilter system hospitals. Parameters measured include the following physical parameters include temperature, TSS, TDS. Chemical parameters include pH, COD, MBAs, BOD5, NH3 Total, Oils and Grease. Microbiological parameters Total coliform. Data were analyzed descriptively. Results showed treatment with a system biofilter anaerobic-aerobic produce effluent quality hospital safely discharged to the environment (meet environmental quality standards) and the results are used as a design student worksheet (LKS) on the biology subject Vocational High School (SMK ) Keywords: Biofilter, Wastewater, Hospital, Student Work Sheet